SISTEM PENUNJANG KEPUTUSAN KELAYAKAN SERTIFIKASI GURU DENGAN MENGGUNAKAN METODE SAW (Simple Additive Weighting) Studi Kasus SMAN 1 Pringsewu - Elisabet Yunaeti Anggraeni; Sudewi Sudewi; Cindi Amelia AW (Jurnal TAM (Technology Acceptance Model), 2016)
ABSTRACTDecision support system is a system that is used to support decision making within an enterprise organization or educational institution. The issue of quality education is a key condition for realizing the nation's life advanced, modern and prosperous. Then the human resources (HR), especially teachers must be maintained and be selected appropriately in order to show a good performance and optimal and quality. From the analysis of the obtained picture that the eligibility decision support system of teacher certification can be done by using SAW (Simple Additive weighting) using a computer that suits your needs, so that use is more easily obtain the results of ranking the better. With the decision support system of teacher certification eligibility is expected to ease in viewing the results of the analysis of teacher certification.